2012
DOI: 10.1186/1756-3305-5-162
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Babesia bovis infection-induced gene expression changes in larvae from the cattle tick, Rhipicephalus (Boophilus) microplus

Abstract: BackgroundCattle babesiosis is a tick-borne disease of cattle that has severe economic impact on cattle producers throughout the world’s tropical and subtropical countries. The most severe form of the disease is caused by the apicomplexan, Babesia bovis, and transmitted to cattle through the bite of infected cattle ticks of the genus Rhipicephalus, with the most prevalent species being Rhipicephalus (Boophilus) microplus. We studied the reaction of the R. microplus larval transcriptome in response to infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Genes involved in immunity, stress, and defense responses showed up-regulation in response to B. bovis infection (Heekin et al, 2012), while genes encoding for calreticulin, kunitz-type serine protease inhibitors and microplusin which exhibits antimicrobial activity, were differentially expressed in B. bovis/B. bigemina infected Rhipicephalus ticks (Rachinsky et al, 2007; Antunes et al, 2012; Heekin et al, 2013; Lu et al, 2016).…”
Section: Biological Processes Involved In Tick-pathogen Interactionsmentioning
confidence: 99%
“…Genes involved in immunity, stress, and defense responses showed up-regulation in response to B. bovis infection (Heekin et al, 2012), while genes encoding for calreticulin, kunitz-type serine protease inhibitors and microplusin which exhibits antimicrobial activity, were differentially expressed in B. bovis/B. bigemina infected Rhipicephalus ticks (Rachinsky et al, 2007; Antunes et al, 2012; Heekin et al, 2013; Lu et al, 2016).…”
Section: Biological Processes Involved In Tick-pathogen Interactionsmentioning
confidence: 99%
“…Although genomic sequences of Babesia and tick are available (Pagel Van Zee et al, 2007; Cornillot et al, 2012) and several projects have identified tick genes differently expressed upon Babesia infection (Rachinsky et al, 2007, 2008; Antunes et al, 2012; Heekin et al, 2012), only few tick genes have been shown to be directly implicated in the vector-pathogen interaction (Figure 4 and Table 3). First of them, called longicin (Tsuji and Fujisaki, 2007), is defensin-like protein of H. longicornis exerting anti-microbial and anti-fungal activity.…”
Section: Tick Interactions With Transmitted Pathogensmentioning
confidence: 99%
“…This tick species is a major problem for livestock production worldwide because it is the biological vector for disease agents causing bovine babesiosis ( Babesia bovis , B. bigemina ) and anaplasmosis ( Anaplasma marginale ) [2]. Along with the closely related cattle tick ( R. annulatus ) it was likely introduced to the New World by Spanish colonialists.…”
Section: Introductionmentioning
confidence: 99%